Role of Artificial Intelligence in Enhancing Information Assurance - Neoaz, Nahid (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Abstract: The unveiling of AI in the supplement of Information assurance is revolutionizing practice of Cybersecurity in organization. Derived from AI enablers of ML and DL, NLP makes a significant contribution in the construction of threat perception, risk management, immediate response, and recovery to incidents than the conventional security. Executive Summary Machine Learning Employment A raw feed of a vast volume of data in advance technology can be fed in on a continuous basis, these data can be filtered, analyzed, verified, interpreted, patterns can be generated, threat identification and threat handling can be done on an automated basis and time loss to threats and time taken for rectifications can be minimized. The value of AI can consequently be justified on the basis of further details within the vulnerability management on the basis of risk prioritization, the analytical approach of patch metallization as well as the detection of new vulnerability, the so-called zero-day-vulnerability; for incident response, AI is of relevance because it uses the analytical potentials of AI in order to immediately contain the event, to drive the recovery process, and during findings analysis. That is why its constant supervision is one of the activities that make AI enhance one or another stabilization of the organizational systems, and provides the prognosis of dangers and the implementation of numerous rehearsing. Therefore, AI as the potential future solution in the sphere of cybersecurity needs to be discussed in connection with the data safety concerns, as well as ethical issues and roles of people. The principal concern of this paper is therefore, on how convenient on information assurance is, with point reference to the aspect of how it can be convenient in helping to elucidate threats, for the purpose of responding independently and in improving the recovery process; notwithstanding, like everything in this world, AI has both advantages and disadvantages that require reconsideration. Which is why AI is a strategic asset that needs to be used to protect organizations and their systems against today’s and tomorrow’s cyber threats.